Influence of Education Level of Older Patients on Polypharmacy, Potentially Inappropriate Medications Listed in Beer’s Criteria, and Unplanned Hospitalization: A Cross-Sectional Study in Lahore, Pakistan - Sarwar, Muhammad Rehan (Medicina (Kaunas), 2018)
Objective: To evaluate influence of education level of older patients on polypharmacy, potentially inappropriate medications (PIMs) listed in Beer’s Criteria, and unplanned hospitalization. Methods: A cross-sectional study was conducted among older people aged ≥65 years between 1 December 2017 and 28 February 2018. For data analysis, descriptive statistics and logistic regression analysis were employed. Results: Among 385 older patients, 88.8% were prescribed PIMs and 56.4% underwent PIMs associated unplanned hospitalization. Older people were less exposed to polypharmacy or excessive polypharmacy as their education levels increased (no formal education vs. primary vs. secondary vs. tertiary, 74% vs. 69.8% vs. 60.5% vs. 58.1%). Patients having higher education were also accompanied by significantly lower prescription of PIMs (no formal education vs. primary vs. secondary vs. tertiary, 96% vs. 87.3% vs. 84.5% vs. 79.1%) as well as unplanned hospitalization (no formal education vs. primary vs. secondary vs. tertiary, 64.7% vs. 76.2% vs. 40.3% vs. 46.5%). Results of regression analysis revealed that no formal education (OR = 1.202, 95% CI = 1.032–2.146, p-value = 0.003) and primary education level (OR = 1.175, 95% CI = 1.014–1.538, p-value = 0.039) were significantly associated with the use of polypharmacy among older people. On the other hand, no formal education was significantly associated with the prescription of PIMs (OR = 1.898, 95% CI = 1.151–2.786, p-value = 0.007). Furthermore, older people with no formal education (OR = 1.402, 95% CI = 1.123–1.994, p-value = 0.010) and primary education level (OR = 1.775, 95% CI = 1.281–3.018, p-value = <0.001) were significantly more likely to undergo unplanned hospitalization. Conclusions: Patients having low literacy level are more likely to receive PIMs, polypharmacy, and undergo unplanned hospitalization in comparison to highly educated patients. Hence, promotion of health literacy for patients is crucial to overcome these problems.